Առևտուրը և տնտեսական բարգավաճումը յոթերորդ դարի Հայաստանում - Տեր-Ղևոնդյան, Արամ (Մատենադարան)
The article reveals the reasons of the commercial-economic and cultural growth in the 7th century Armenia. Both Byzantine and Persian parts of Armenia gained relative autonomy at the end of the 6th century and in the 30s of the 7th century they were reunited. Up to the end of the 7th century, while Armenia was deprived of a king, the “Prince of Armenia” played a unifying role in the country. Thanks to the temporary military and political balance between the Arab Caliphate and Byzantium, Armenia enjoyed some independence and paid only an insignificant tribute. Moreover, the international transit trade was carried on via the Araxes valley, generating considerable profit for Armenia. An unprecedented construction movement started in the country; in particular, huge temples were built. On the basis of the foregoing, the author considers this centenary (late 6th – late 7th cc.) as a specific phase in the history of Armenia, separating it from the so-called “Marzban” (5th–7th cc.) and Arab (7th–9th cc.) periods. Автор раскрывает причины торгово-экономического и культурного подъема Армении в VII веке. Византийская и персидская части Армении с конца VI в. получили относительную самостоятельность, а с 30-ых гг. VII века воссоединились. До конца VII века, при отсутствии царской власти “Князь Армении” играл объединяющую роль в стране. Благодаря временному военно-политическому равновесию между Арабским халифатом и Византией, Армения пользовалась некоторой независимостью и выплачивала ничтожнюю подать. Более того, транзитная международная торговля велась через долину реки Аракс, принося Армении большую прибыль. Именно за счет этого небывалое развитие получило строительство, особенно возведение крупных храмов. На основании вышесказанного автор рассматривает это столетие как отдельный этап в истории Армении, отделяя его от “марзпанского” (V-VII вв.) и Арабского (VII-IX вв.) периодов.
Keywords: Հայ ժողովրդի պատմություն; Մշակույթ